Valorization of monovarietal Nostrana di Brisighella extra virgin olive oils: focus on bioactive compounds - Enrico Casadei; Enrico Casadei; Enrico Valli; Enrico Valli; Alessandra Bendini; Alessandra Bendini; Sara Barbieri; Rosalba Tucci; Federico Ferioli; Tullia Gallina Toschi; Tullia Gallina Toschi (Frontiers in Nutrition, 2024)
A “green breakthough” at the table due to consumer demand for healthy and sustainable foods, which aligns with the typical Mediterranean diet, has recently led to an increase in the consumption of products such as extra virgin olive oil. In fact, Italian olive cultivation, which contributes an average of 15% of world production, has seen the production of extra virgin olive oil with a value of exports that have doubled in the last 20 years. In this context, the olive oil sector of the Emilia-Romagna region (Italy), and in particular the PDO Brisighella, could achieve greater success with consumers by proposing a product obtained through sustainable agriculture that enhances the content of bioactive compounds. For these reasons, in this study, different agronomic variables are investigated in order to optimize the presence of bioactive components in extra virgin olive oil made from monovarietal Nostrana di Brisighella, namely phenolic and positive volatile compounds, thus naturally enriching this product both from health and sensory points of view. The study focuses on the volatile and phenolic fractions (derivatives of hydroxytyrosol and tyrosol) of olive oil and the positive sensory attributes (fruity, bitter and pungent) that are known to be associated with these molecules. The phenolic content is of particular interest due to the potential to support health claims. Extra virgin olive oil samples were produced from olives of the Nostrana di Brisighella cultivar; fruits were obtained through integrated pest management or organic farming and picked at four increasing indices of maturity, corresponding to four successive weeks of harvesting. These agronomic variables influenced the compositional and sensory characteristics of the extra virgin olive oils assessed, highlighting differences that likely derive from the effect of the agronomic system used, i.e., integrated pest management or organic farming.